The motive of the bride search in the heroic epics of the Turkic peoples - Usipbayeva П.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
The Turkic epic is a treasure of the spiritual and cultural heritage of the Turkic peoples, passed down from generation to generation. Heroic epic is a narrative poem that tells about heroic life and feats of arms of warriors, possessed of great strength, defending the tribes and the individual families from the attacks strangers who saved the people from heavy disaster. In oral literature in the understanding of the people the word «batyr» means brave, fair, strong man-hero.One of the characteristic themes of the Turkic epic is the motive of the bride’s search for a hero. When classifying the motives of the characters in the epos, it can be concluded that they are a continuation of the ancient plot traditions. The article discusses the motives and plots of the search for the bride’s hero as part of the cultural heritage of the Turkic peoples